DAMPAK MEDIA SOSIAL TIKTOK PADA AKHLAK ANAK-ANAK DI KOTA MAKASSAR (Fakultas Dakwah dan Komunikasi, 2022)
The main problem in this study is how TikTok Social Media develops among children in Makassar City. Then the subject matter is broken down into several sub-problems or research questions, namely, First, how does the impact of the use of TikTok Social Media on children's morals in Makassar? Secondly, how are parents' efforts in overcoming the negative impact of TikTok Social Media in Makassar? The type of research used in this research is qualitative research, which is directly into the field describing phenomena, information, and data in the field related to what has been done. The data sources in this study are parents, children, and the community. The subjects in this study were children on Jalan Mirah Seruni which numbered 15 people. The data collection techniques used in this study are observation, interviews, and documentation. Data validity techniques include data triangulation. The data analysis technique used is Descriptive Analytics. The implication of this study is that the impact of TikTok social media is not always negative, but there are also positive things that exist. If used well, it will have a positive impact and vice versa. It all depends on how we use it. With TikTok, Social Media needs to be used with a good purpose just like Following the movements that are liked on TikTok and it is good to imitate, it will train memory, to train mentally to appear in public, and train children's creativity.